COMPARATIVE CLINICAL ELECTRONEUROPHYSIOLOGICAL CHARACTERISTICS OF CHRONIC MIGRAINE - A. A. Yakupova; R. A. Yakupov (Медицинский совет, 2017)
Clinical electroneurophysiological mapping was performed in 30 patients with chronic migraine, in 41 patients with migraine without aura and in 40 patients with chronic headache of tension. In addition to the clinical examination psychological testing and polysynaptic blink reflex were used. It was established that an important neurophysiological phenomenon in chronic migraine is the increase in polysynaptic reflex excitability. It characterizes the failure of central inhibition and inefficiency of antinociceptive control in this disease.